Project Apollo: The Genstar Report and the City of Calgary, 1973–1975 - Foran, Max (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractThis article focuses on a secret study commissioned by the City of Calgary chief commissioner in 1973 to ascertain the extent and threat of monopoly control by a leading land developer in the city. Kept from City Council for months after its completion, the report, code named Apollo, found that the Genstar group of companies was in a strong monopoly position. When released, the report led to a public debate, political infighting at City Hall, threats of legal action by Genstar, and a federal investigation. Though its findings on monopoly implications were never substantiated, the report did indicate the growing concentration of corporate power in the land development and construction industries in Calgary, and likely in other Canadian cities as well.